Public care policies for child and adolescent victims of domestic violence Las políticas públicas de atención al niño y las víctimas juveniles de violencia doméstica As políticas públicas de atendimento à crianca e ao adolescente vítimas de violência doméstica - Telma Sanchez Vendruscolo; Maria das Graças Carvalho Ferriani; Marta Angélica Iossi Silva (Universidade de São Paulo, 2007)
This is a qualitative study that aimed to know and analyze the social representations of social workers regarding the assistance to the child and adolescent, victims of domestic violence. The data collection was carried out through semi-structured interviews and participant observation. The data analysis was based on the hermeneutic-dialectic perspective. The empirical categories that emerged from the subjects' representations were: "lack of policy", "do not support because have not received support", and "social assistance" whereas the political economic aspect was highlighted as determinant of violence; the cultural aspects, perpetuating a cycle of violence in the families. An important step must be taken is the formulation of public policies directed to all children and adolescents and not policies of exception, directed only to those who are in situation of "social and personal risk". Se trata de un estudio con aproximación cualitativa que buscó conocer y analizar las representaciones sociales de los trabajadores sociales acerca de la atención al nino y al adolescente víctimas de violencia doméstica. Para la recolecta de los datos, utilizamos entrevistas semiestructuradas y observación participante. El análisis de los datos se inspiró en la hermenéutica dialéctica. Las categorías empíricas que emergieron de las representaciones de los sujetos fueron: "ausencia de política", "no coger en los brazos porque no fue cogido" y "atención social" sobresaliendo el aspecto político-económico como determinante de la violencia; los aspectos culturales, perpetuando un ciclo de la violencia en las familias. Un paso importante que se debe dar es la formulación de políticas públicas para todos los niños y adolescentes y no políticas de excepción, solamente para aquellos en situación de "riesgo personal y social". Trata-se de um estudo de abordagem qualitativa que buscou conhecer e analisar as representações sociais dos trabalhadores sociais em torno do atendimento à criança e ao adolescente vítimas de violência doméstica. Para coleta dos dados, utilizamos entrevistas semi-estruturadas e observação participante. A análise dos dados inspirou-se na hermenêutica dialética. As categorias empíricas que emergiram das representações dos sujeitos foram: "ausência de política", "não dar colo porque não teve colo" e "atendimento social", sobressaindo o aspecto político-econômico como determinante da violência e os aspectos culturais, perpetuando um ciclo de violência nas famílias. Um passo importante que deve ser dado é a formulação de políticas públicas para toda criança e adolescente e não políticas de exceção, somente para aqueles em situação de "risco pessoal e social".